Inter-association and path coefficient analysis for yield and yield attributing traits in ash gourd [Benincasa hispida (Thunb) Cogn.] - Hament Thakur* and Vijay Kumar (Electronic Journal of Plant Breeding)
Twenty nine genotypes of ash gourd (land races and released varieties) were evaluated during summer season (March to July) of 2022 and 2023. The main objective of the study was to evaluate the inter-associations among 15 yield and yield attributing traits, and estimate the direct and indirect effects of these traits on yield. Yield per plot (YPP) was significantly and positively correlated with number of fruits per plot (FPP), average fruit weight (AFW), equatorial diameter of fruit (ED), length of seed (LoS), width of seed (WdoS), weight of 100 seed (WoS), thickness of flesh (ToF) and equatorial diameter of cavity (EDC). The present study also revealed high positive direct effect of equatorial diameter of fruit (ED), fruit shape index (FSI), percent proportion of cavity (PPC), AFW, FPP and LoS on yield per plant. The combined results of path analysis and correlation coefficients indicated that AFW, ED, LoS, Wdos, WoS, Tof , EDC FSI and FPP are important yield attributing traits and more emphasis should be given to these traits, while going for selection of high yielding genotypes.